Prognostic value of nighttime blood pressure load in Chinese patients with nondialysis chronic kidney disease. Issue 9 (7th May 2017) - Li, Yan; Deng, Qiongxia; Li, Huiqun; Ma, Xinxin; Zhang, Jun; Peng, Hui; Wang, Cheng; Lou, Tanqi
Abstract: The prognostic value of nighttime blood pressure (BP) load in patients with chronic kidney disease (CKD) remains unknown. The prognostic value of nighttime BP load in a cohort of Chinese patients with nondialysis CKD was investigated. The authors monitored ambulatory BP and followed health outcomes in 588 Chinese CKD patients. Multivariable‐adjusted Cox regression analyses indicated that nighttime BP load was a significant risk factor for all clinical outcomes in CKD patients, even when adjusted for clinic BP. Tertile 3 of systolic BP load (vs tertile 1) was associated with an increased risk of renal events (hazard ratio [HR], 2.21; 95% confidence interval [CI], 1.12–4.38) and cardiovascular events (HR, 5.34; 95% CI, 1.58–18.04); tertile 3 of diastolic BP load (vs tertile 1) was associated with an increased risk of all‐cause mortality (HR, 6.73; 95% CI, 1.79–25.20), cardiovascular mortality (HR, 7.18; 95% CI, 1.47–35.03), renal events (HR, 2.40; 95% CI, 1.17–4.92), and cardiovascular events (HR, 5.87; 95% CI, 1.97–17.52). Higher nighttime BP load, especially nighttime diastolic BP load, was associated with a poorer prognosis in Chinese nondialysis CKD patients.